Correspondencia entre William H. Hunt a Roberto H. Todd - Moscicki, Ignacio; Hunt, William H.; Todd, Roberto H. (My University, 1939)
Carta relacionada a la bandera puertorriqueña de 1895.
Keywords: Flags--Puerto Rico.; Bandera--Puerto Rico.